2021
DOI: 10.1038/s41598-021-96957-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein electrophoretic pattern in piglets during the early postnatal period

Abstract: The pattern of serum proteins, the typical features of the electrophoretogram in newborn piglets and during their postnatal development is not completely described. Therefore, the aim of this study was to characterize the changes in serum protein electrophoretic pattern and features of the electrophoretograms during the early postnatal period. Significant changes during the monitored period were found in all evaluated parameters (P < 0.001). The most marked changes were observed mainly in the period before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…In these animals, antibodies are secreted in the maternal milk and subsequently must be passively received by the fetus from colostrum [65]. The γ-globulin concentrations obtained in this study are comparable to those presented previously in neonatal ruminants [29,31], but comparative studies were not yet performed. The results suggest that electrophoresis may be an important laboratory diagnostic aid to monitor perinatal serum protein electrophoretic pattern and the distribution of serum proteins in newborns of farm animals.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In these animals, antibodies are secreted in the maternal milk and subsequently must be passively received by the fetus from colostrum [65]. The γ-globulin concentrations obtained in this study are comparable to those presented previously in neonatal ruminants [29,31], but comparative studies were not yet performed. The results suggest that electrophoresis may be an important laboratory diagnostic aid to monitor perinatal serum protein electrophoretic pattern and the distribution of serum proteins in newborns of farm animals.…”
Section: Discussionsupporting
confidence: 80%
“…The proportion of albumin was higher than 50% in all the evaluated ruminant species, but the study showed differences in its concentrations between calves, lambs, as well as goat kids. Although the measured values were comparable to those presented previously [29][30][31], comparison studies between different animal species were not yet performed. Variations in the amino acid composition of the albumin, structure and binding sites for ligands were observed among different animal species [32].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…[ 33 ] The concentrations of serum proteins in newborn piglets are very low; therefore, adequate biosynthesis and transportation of proteins are essential for their survival of newborn piglets. [ 34 ] Bile secretion is a crucial biochemical process in newborn piglets, and bile acids (the main component of bile) play a central role in the emulsification of luminal fat and participate in the normal fetal development and growth of piglets. [ 35 ] In addition, the metabolites matching these pathways were mainly decreased in Duroc pigs compared to those in the TB and XB pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of viremia in the experimental group may be explained by lower levels of neutralizing antibodies against PCV2 due to the use of intradermal vaccination. The level of total protein in blood serum is determined by the combined concentration of its various fractions (Tóthová et al, 2021). Albumin is one of the most common plasma proteins, and its level is typically used as an indicator of liver or kidney function (Carvalho and Machado, 2018;Friedman and Fadem, 2010).…”
Section: Discussionmentioning
confidence: 99%